Association between self-reported menstrual disorders and occupational exposures in female healthcare workers: a university hospital experience from Turkey - Güngördü, Nejdiye; Kurtul, Seher (The European Research Journal, 2023)
Objectives: This study aims to demonstrate the relationship between menstrual disorders and occupational exposures in female healthcare workers, and to contribute to the regulation and improvement of working conditions of female healthcare workers. Methods: A cross-sectional study among 503 female healthcare workers at university hospital in Turkey was conducted during December 2020-April 2021. The questionnaire prepared using the Google Forms program was sent electronically. Results: Prevalence of dysmenorrhea was 59%, abnormal amount of menstrual bleeding 48.7%, abnormal menstrual duration 32%, and abnormal menstrual cycle length 154 30.6% in 503 participants. Dysmenorrhea risk was 0.79-fold (95% CI = 0.64-0.83) lower in those with advanced age and 1.56-fold (95% CI = 1.02-2.37) higher in smokers; risk of abnormal amount of menstrual bleeding was 3.91-fold (95% CI = 1.24-12.30) higher in those with total employment time of ≥ 20 years and 1.56-fold (95% CI = 1.07-2.26) higher in those who worked with display screens for > 20 hours a week; risk of abnormal menstrual cycle length was 3.46-fold (95% CI = 1.41-8.43) higher in technicians, 2.86-fold (95% CI = 1.24-6.61) higher in nurses, 2.63-fold (95% CI = 1.19-5.79) higher in other healthcare workers, and 2.14-fold (95% CI = 1.42-3.21) higher in those who were unsatisfied with their job. Conclusions: It was found that occupational exposures may increase the risk of menstrual disorders. A plan of action is needed to reduce the frequency of menstrual disorders by preventing occupational exposures experienced by healthcare workers.